Modified four-pass differential SAR interferometry for estimating mountain glacier surface velocity fields. Issue 1 (2nd January 2016) - Liu, Guang; Guo, Huadong; Yue, Huanyin; Perski, Zbigniew; Yan, Shiyong; Song, Rui; Fan, Jinghui; Ruan, Zhixing
ABSTRACT: Conventional four-pass differential synthetic aperture radar interferometry (DInSAR) assumes that there are no significant changes in the ground during the period between the acquisition times of SAR images for topographic DInSAR pairs. This assumption can rarely be satisfied for glacial areas due to their continuous movement. This letter proposes a modified four-pass DInSAR method without an external digital elevation model (DEM), taking into account glacier movement between the acquisition times of SAR images used to form topographic DInSAR pairs. An explicit expression of theoretical formulas for a modified four-pass DInSAR technique was derived for the first time, revealing that four-pass DInSAR considering ground movement of topographic pairs was equivalent to that of conventional four-pass DInSAR with a spatially varying nominal wavelength. Then the proposed method was tested with four Advanced Land Observing Satellite (ALOS) SAR images covering Dongkemadi glacier located on the Tibetan Plateau, China. An experiment with real data showed that the proposed method could obtain glacial flow patterns efficiently, and that the difference between two-pass DInSAR and the proposed method is a result of DEM bias and glacial thinning. The approach presented in this letter proved to be appropriate for monitoring glacial motion and provides a valuable tool for glacier studies, without the need of an external DEM.